FAKTOR-FAKTOR RISIKO KEJADIAN DEMAM BERDARAH DENGUE (DBD) DAN PEMETAAN RESISTENSI NYAMUK AEDES AEGYPTI DI KECAMATAN WONOGIRI KABUPATEN WONOGIRI TAHUN 2010 - , Purnama Magdalena Simanullang, dr. Tribaskoro Tunggul S., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
HF Background: Dengue hemorrhagic fever is a problem in tropical and sub tropical countries. In Wonogiri District, the IR of DHF cases in 2009 was 3.64 per 10,000 population with CFR of 0.52%, distributing in 13 sub districts and 48 villages having DHF endemics. Wonogiri sub district is a D endemic with IR of the cases in 2009 was 14.86 per 10,000 population with CFR of 1.43%. The factors of DHF incidences, the resistance of Aedes aegypti on insecticide used for DHF controlling and case dispersion pattern which is not yet known. ces Objective: To obtain a description on dispersion pattern of DHF patients and to find out risk factors that were related to DHF inciden in Wonogiri sub district in 2010 that included educational level, occupation status, Maya index, and mosquito resistance. ir - Method: This was an observational-analytical study with pa matched case-control study design. Quantitative data analyses used univariable analysis with frequency distribution, bivariable analysis with chi-square (Ï 2 ) test according to McNemar, multivariable analysis with conditional logistic regression, insecticide resistance with standard deviation of Absorbance Value (AV) and cluster with nearest neighbour analysis. T here was not a signi Result: ficant relationship between educational level and DHF incidences (p value > 0.05). Unemployed (p value = 0,0017, OR = 4,8